Siloxane-functionalised surface patterns as templates for the ordered deposition of thin lamellar objects - Hoffmann, Julian; Wacker, Irene; Schröder, Rasmus R. (Scientific reports, 2019)
A novel method is demonstrated for ordered deposition of thin lamellar objects from a liquid environment onto solid substrates by solid/fluid/solid-driven organisation. Surface functionalisation forms a template pattern that accumulates the lamellar objects by site-selective wetting of the target area without the need for a physical fluid containment. Contrary to conventional handling methods, no mechanical contact occurs, which facilitates the ordered deposition without wrinkles or ruptures. An additive and a subtractive process for the creation of such templates are presented. The subtractive process starts with the complete silanisation of the substrate in the vapour phase followed by site-selective oxygen plasma treatment of the siloxane film. The additive process uses microcontact printing to transfer the target pattern. Both processes are characterised by optical inspection of the wetting contours and it is found that site-selective plasma treatment shows a better pattern fidelity. The patterns obtained by site-selective plasma treatment are also subject to ToF-SIMS analysis and show good chemical contrast between hydrophilic and hydrophobic areas. The ordered deposition of lamellar objects by this new method is demonstrated for 60 nm thick ultramicrotome sections of epoxide resin on pre-patterned glass substrates.
Gesehen am 09.01.2020